Two new eudesmanolides from sphaeranthus indicus (Linn) - Jadhav, Ravindra B.; Sonawane, Kiran B.; Deshpande, Nirmala R.; Rojatkar, Supada R. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2007)
Two new eudesmanolides have been isolated from the aerial part of Sphaeranthus indicus and their structures have been established as 11 alpha,13-dihydro-3 alpha,7 alpha-dihydroxyeudesm-4-en 6 alpha, 12-olide 1, 4-en-6 beta,7 alpha-eudesmanolide 3, on the basis of spectral data and comparison of spectral data with those of reported data of compounds 2, 4 and 5.
Keywords: eudesmanolides; olide; Sphaeranthus indicus